HUBUNGAN KEPUASAN KERJA PERAWAT DENGAN MISSED NURSING CARE DI RUANG RAWAT INAP RS. X KOTA BATAM - Sri Muharni; Utari CH Wardhani; Efrida Mayasari (Jurnal Ilmu Keperawatan, 2022)
Missed nursing care is a global challenge that threatens patient safety and health. Missed nursing care phenomenon, most (55-98%) nurses leave one or more nursing care. One of the nurse's roles is to provide nursing care to patients safely without anything being missed or delayed. One of the factors causing Missed nursing care is job satisfaction. A nurse who isdissatisfied in doing her job will often feel burdened at work so that the level of patient safety is disrupted. Phenomenon found in RS. X the number of phlebitis, urinary tract infections and the incidence of decubitus this happened due to the negligence of nurses in providing nursing care. This study was conducted to see the relationship between job satisfaction and Missed nursing care. The design used in this study was cross sectional with a total sampling technique of 47 nurses. The results of the bivariate analysis showed that 15 nurses (94%) had a low perception of job satisfaction with high Missed nursing care. The results of statistical tests using the Chi- square test obtained pvalue 0.000